Trusted Systems Second International Conference, INTRUST 2010, Beijing, China, December 13-15, 2010, Revised Selected Papers - Chen, Liqun; Yung, Moti.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the International Conference on Trusted Systems, INTRUST 2010, held in Beijing, China, in December 2010. The 23 revised full papers were carefully reviewd and selected from 66 submissions for inclusion in the book. The papers are organized in seven topical sections on implementation technology, security analysis, cryptographic aspects, mobile trusted systems, hardware security, attestation, and software protection.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Computers and Society; Systems and Data Security